Passing it on during a day in the life of resilient adolescents in diverse communities around the globe - Catherine Ann Cameron (2018)
This social-ecological inquiry explores youth resiliency in diverse communities using innovative qualitative visual methodologies. It engages adolescents in a process of sharing their daily experiences and reflecting on the resources they bring to bear to thrive in the face of geographic and social relocations. The four youth participants were identified by local community advisors as especially resilient teenagers despite experiencing transitions that could provoke risks to normative development. The youths were interviewed and videotaped during a weekend day in [their] lives. They also engaged in deliberations on that day; took part in a photo elicitation that reflected on significant people, places, and objects in their environments; and responded to a resilience questionnaire. These visual data and the youths' deliberations were analyzed for themes of positive identity and personal control observed within and across communities by their passing on the nurturant interchanges they themselves had experienced during that day. © Springer Science+Business Media, LLC 2009.